2020
DOI: 10.3389/fmicb.2020.01977
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence That Homologs of Key Circadian Clock Genes Direct Circadian Programs of Development or mRNA Abundance in Verticillium dahliae

Abstract: Many organisms harbor circadian clocks that promote their adaptation to the rhythmic environment. While a broad knowledge of the molecular mechanism of circadian clocks has been gained through the fungal model Neurospora crassa, little is known about circadian clocks in other fungi. N. crassa belongs to the same class as many important plant pathogens including the vascular wilt fungus Verticillium dahliae. We identified homologs of N. crassa clock proteins in V. dahliae, which showed high conservation in key … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…In fungi, little is known about FRQ function besides N. crassa and B. cinerea . A recent study of frq in the phytopathogen V. dahliae found no significant phenotypic differences in the deletion strain regarding sporulation and microsclerotia formation in DD or LD ( Cascant-Lopez et al, 2020 ). Similarly, in the entomopathogenic fungi Metarhizium robertsii , FRQ is necessary for ring formation under LD 12:12, although neither the WT nor the mutant strain displayed such rings under DD conditions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In fungi, little is known about FRQ function besides N. crassa and B. cinerea . A recent study of frq in the phytopathogen V. dahliae found no significant phenotypic differences in the deletion strain regarding sporulation and microsclerotia formation in DD or LD ( Cascant-Lopez et al, 2020 ). Similarly, in the entomopathogenic fungi Metarhizium robertsii , FRQ is necessary for ring formation under LD 12:12, although neither the WT nor the mutant strain displayed such rings under DD conditions.…”
Section: Discussionmentioning
confidence: 95%
“…These findings reinforce the importance of defined nutrient/temperature conditions to monitor the clockworks and help future fungal circadian studies visualize otherwise weak oscillations, like those observed in Pyronema confluens and Ophiocordyceps kimflemingiae ( de Bekker et al, 2017 ; Traeger and Nowrousian, 2015 ). This could also help monitor frq molecular oscillations in fungi where previous attempts have failed, like in Verticillium dahliae, Aureobasidium pullulans, and Magnaporthe oryzae ( Cascant-Lopez et al, 2020 ; Deng et al, 2015 ; Franco et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype of light-induced frq expression has been observed in other Ascomycota such as the soil-living saprophyte Pyronema confluens (Pezizomycetes) 59 , as well as in the Mucoromycota, such as the arbuscular mycorrhizal fungus R. irregularis 26 . The presence of frq, wc-1 , and wc-2 alone, however, is not enough to infer a functional FWO oscillator: in the plant pathogen Verticillium dahliae, the frq homolog is present, but is largely unresponsive to light 60 . It is thus noteworthy that, in the present study, we observe that lichen-forming fungi from two highly diverged lineages, the Lecanoromycetes ( U. pustulata ) and the Eurotiomycetes ( D. miniatum ) both display frq light - dependent responses similar to the canonical responses of N. crassa , pointing to a functionally-conserved core circadian clock mechanism in at least two highly-diverged groups of lichen-forming fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other Ascomycetes, Z. tritici can sense and respond to light by inducing morphological changes during its mycelial development [ 24 , 25 , 26 ]. Its light-sensing capacity could be ascribable to the multiple photoreceptor homolog genes coded in the Z. tritici genome such as the blue-light receptor white collar-1 ( Ztwco-1 ), VIVID, cryptochromes, photolyases, and phytochromes [ 27 , 28 ]. In particular, Ztwco-1 regulates light detection and controls the hyphal morphology, production of pycnidia, and micropycnidiospores [ 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%